Legal Protection for Owners of Well-Known Trademarks Viewed from the Principle of Well-Known Marks - Jeannet Kunta Adjie; Christine Kansil (Journal of Law, Politic and Humanities, 2024)
Legal protection for owners of well-known trademarks is a crucial topic in the context of increasingly competitive business environments. Well-known trademarks not only represent the quality of products but also reflect the reputation and image of a company. The principle regarding well-known marks plays an essential role in safeguarding such trademarks from any form of misuse and imitation, which can cause harm to both the trademark owner and consumers. This research aims to delve deeper into the legal protection afforded to owners of well-known trademarks. The methodology employed in this research is normative legal research, focusing on the exposition of concepts and doctrines within legal science. The findings of this study indicate that trademarks meeting the criteria for well-known status, as stipulated in positive law, are entitled to absolute legal protection. This means that if another party uses the same or imitates a well-known trademark, the trademark owner has the right to pursue legal action. In today’s business era, we frequently encounter many well-known trademarks, both domestic and foreign. Therefore, it is essential to secure these well-known trademarks to prevent potential misuse in the trade of goods and services. Such protection is not only beneficial for trademark owners but also for consumers.